Volitional assessment of respiratory muscle strength - J.W. Fitting (Monaldi Archives for Chest Disease, 2015)
Respiratory muscle weakness may induce dyspnoea, secretion retention and respiratory failure. Assessing respiratory muscle strength is mandatory in neuromuscular diseases and in case of unexplained dyspnoea. A step by step approach is recommended, starting with simple volitional tests. Using spirometry, respiratory muscle weakness may be suspected on the basis of an abnormal flowvolume loop or a fall of supine vital capacity. When normal, maximal inspiratory and expiratory pressures against a near complete occlusion exclude significant muscle weakness, but low values are more difficult to interpret. Sniff nasal inspiratory pressure is a useful alternative because it is easy and it eliminates the problem of air leaks around the mouthpiece in patients with neuromuscular disorders. The strength available for coughing is easily assessed by measuring peak cough flow. In most cases, these simple non invasive tests are sufficient to confirm or to eliminate significant respiratory muscle weakness and help the timely introduction of ventilatory support or assisted cough techniques. In a minority of patients, a more complete evaluation is necessary using non volitional tests like cervical magnetic stimulation of phrenic nerves.